Theoretical analysis of the power generation of pumping cycle kite power systems compared to traditional wind turbines in Aberdeen - Ye, Zhihui; Chaer, Issa; Hartungi, Rusdy; Ross, Marcus (Frontiers in Built Environment, 2023)
The United Kingdom (UK) has pledged to reduce its greenhouse-gas emissions to net zero by 2050. However, in July 2022, the High Court ruled that the government’s net zero strategy failed to outline policies that would enable it to meet the target. As a result, the government published a new plan that sets out opportunities for innovative technologies like Floating Offshore Wind Manufacturing, and hydrogen, which will not only help us reach net zero. For wind, the government’s goal is to develop up to 50 GW of offshore wind by 2030. The challenge of such an expansion is huge. It means the United Kingdom will need to install an estimated 3,200 new, and much larger, wind turbines by 2030—roughly three new turbines every 2 days. Airborne Wind Energy (AWE) systems are part of a new class of wind energy converters that is receiving considerable attention in the renewable energy generation arena. AWE systems benefit from the steadier and stronger wind streams at high altitudes to generate more energy from wind while avoiding the expense of tower construction. This paper presents a feasibility study of using AWE systems in the UK and particularly in the City of Aberdeen to generate renewable energy. The characteristics of wind energy distributions were theoretically investigated by developing a wind speed distribution model, and then the annual power production of a kite system and a turbine system with 30 kW generator were analysed by applying the annual wind profile in Aberdeen to the performance models of these two systems. It was found that the annual power production of the kite system was two times higher than that of a normal turbine system.